2020
DOI: 10.1017/s1431927620024587
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Effects in Voltage Pulsed Atom Probe

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Products of molecular dissociation are subjected to Coulomb repulsion, which can affect the ion trajectories (Muller et al, 2011; Blum et al, 2016). Additionally, the relative change in mass for the individual dissociation products will influence their ion trajectories (Rousseau et al, 2020). The bimodal trend observed in Al-N 2 + was not apparent in the single-nitride (14 Da) Al-N + pairs, suggesting a unique chemical dissociation path for evaporation of Al-N 2 + molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Products of molecular dissociation are subjected to Coulomb repulsion, which can affect the ion trajectories (Muller et al, 2011; Blum et al, 2016). Additionally, the relative change in mass for the individual dissociation products will influence their ion trajectories (Rousseau et al, 2020). The bimodal trend observed in Al-N 2 + was not apparent in the single-nitride (14 Da) Al-N + pairs, suggesting a unique chemical dissociation path for evaporation of Al-N 2 + molecules.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the multi-hit events are mainly associated with potential errors in compositional accuracy resulting from preferential signal loss (Thuvander et al, 2013; Meisenkothen et al, 2015; Peng et al, 2018; Engberg et al, 2019; Cuduvally et al, 2020); however, statistical analysis of ion pairs within multi-hit detector events can yield significant information relating to the compositional biases (Saxey, 2011; Rousseau et al, 2020; Schwarz et al, 2020). Licata et al found that the percentage of multi-hit events increases with increased Al concentration (Al x Ga 1− x N from x = 0 to 1.0), suggesting that the relative field evaporation required for single Al and N ions is higher than the field required to evaporate AlN pairs and that, conversely, the field required to evaporate single Ga and N ions is less than GaN pairs (Licata et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This artifact will also be present in our LEAP 5000XS machine where non-correlated evaporation is taking place and it would occur in a voltage-pulsed APT experiment. In contrast to normal APT operation, they were evident in our experiments because of the abundance of light imaging gases (Rousseau et al, 2020) and because we kept the standing voltage constant, prevented this artifact being smeared. One obvious solution would be to employ laser pulsing in our future aFIM experiments until this issue can be resolved.…”
Section: Ripples In Mass-to-charge Spectrummentioning
confidence: 86%
“…This was seenthere was one cluster at (1,20) representing the (H + /Ne + ) co-evaporation and another cluster at (4,20) representing the (He + /Ne + ) co-evaporation. The artefact and its phenomena at (4,20), has been explained recently (Rousseau et al, 2020) and the ripples can be thought of as a continuation. Away from these points, the curving lines passing through these points are generally shifted to larger masses because they evaporate at a lower voltage and so attain less energy.…”
Section: Ripples In Mass-to-charge Spectrummentioning
confidence: 98%
See 1 more Smart Citation